2008
DOI: 10.1111/j.1440-1843.2008.01285.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of pulmonary aspiration: A mouse model using a starch granule test in bronchoalveolar lavage

Abstract: The detection of starch granules in BAL is a simple and highly specific method for the diagnosis of PA in an experimental model. Clinical studies using the starch granule detection method in BAL should be tested in at risk patients to evaluate the utility of this method for investigating PA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In a murine model, detection of starch granules in BAL was superior to LLAM index; the latter had a low specificity while the presence of starch granules in the BAL yielded 100% sensitivity and specificity for aspiration. The LLAM index was not different in mice that had starch aspiration versus those who had Pseudomonas aeruginosa instilled in their airways [60]. Similar conclusions came from human studies.…”
Section: Pathophysiologymentioning
confidence: 70%
“…In a murine model, detection of starch granules in BAL was superior to LLAM index; the latter had a low specificity while the presence of starch granules in the BAL yielded 100% sensitivity and specificity for aspiration. The LLAM index was not different in mice that had starch aspiration versus those who had Pseudomonas aeruginosa instilled in their airways [60]. Similar conclusions came from human studies.…”
Section: Pathophysiologymentioning
confidence: 70%
“…Pinto et al describe a mouse model of aspiration in a technical report to Respirology and found that the detection of starch granules in BAL is a simple and highly specific method for the diagnosis of aspiration. 53 In contrast, the better known 'lipid-laden macrophages' were found in all mice irrespective of aspiration. Clinical studies using the starch granule detection method in BAL should be considered to investigate if this approach allows better diagnostic of paediatric patients at risk for repeated and/or chronic aspiration.…”
Section: Technical Aspects In Lung Biology and Diseasementioning
confidence: 88%
“…Pinto et al. describe a mouse model of aspiration in a technical report to Respirology and found that the detection of starch granules in BAL is a simple and highly specific method for the diagnosis of aspiration 53 . In contrast, the better known ‘lipid‐laden macrophages’ were found in all mice irrespective of aspiration.…”
Section: Technical Aspects In Lung Biology and Diseasementioning
confidence: 99%
“…Additional markers of aspiration (e.g., pepsin, radioactive tracers such as Technetium-99m, or food additives might better provide evidence for recurrent aspiration and its role in chronic lung disease [9, 21, 22]).…”
Section: Discussionmentioning
confidence: 99%